The runic inscriptions of Tevsh mountain (Studia Archaeologica, 2024)
The article introduces a single line of runic inscriptions that have been discovered and documented on Mount Tevsh, situated at a distance exceeding 20 km from the center of Bogd Soum in Övörkhangai Province. However, this particular line is unstudied, and two another inscriptions have just been found. The inscription was apparently unearthed in either 1948 or 1962 by a field research team under the leadership of A.P.Okladnikov. The words bän, meaning ‘I’, and qara boduna, meaning ‘common people’, are evident in the text from which the inscription was transcribed. However, due to its incomplete nature, it is not feasible to ascertain the presence of further words and their respective meanings. The inscriptions are written with sharp tools and belong to the type of incised inscriptions.Тэвшийн руни бичээсүүдТовчлол. Тус өгүүлэлд Өвөрхангай аймгийн Богд сумын төвөөс 20 гаруй км-т орших Тэвш уулнаас илрүүлж тэмдэглэсэн ч судалгааны эргэлтэд ороогүй өнөөг хүрсэн нэг мөр руни бичээс болон шинээр илрүүлсэн 2 бичээсийг танилцуулж байна. Уг бичээсийг А.П.Окладниковын удирдсан хээрийн шинжилгээний анги 1948, эсвэл 1962 оны аль нэгэнд илрүүлсэн бололтой. Бичээсийг хуулсан гар хуулбарт  bän- би, qara boduna – харц ард гэсэн үгс маш тодорхой байгаа боловч бүрэн хуулбар биш тул өөр ямар үг байгаа, ямар агуулгатайг тодорхойлох боломжгүй байна. Бичээсийг хурц үзүүртэй багаж зэвсгээр зурж бичсэн, руни бичгийн дурсгалын зураасан бичээсийн төрөлд хамаарах дурсгал юм.Түлхүүр үг. Өвөрхангай аймаг, Богд сум, Тэвш уул, руни бичиг